Pemberian Fikosianin Spirulina Meningkatkan Jumlah Sel Darah, Aktivitas Fagositosis, dan Pertumbuhan Ikan Kerapu Bebek Juvenil (ADMINISTRATION OF SPIRULINA PHYCOCYANIN ENHANCES BLOOD CELLS, PHAGOCYTIC ACTIVITY AND GROWTH IN HUMPBACK GROUPER JUVENILE) - Satyantini, Woro Hastuti; ., Sukenda; Harris, Enang; Utomo, Nur Bambang Priyo (Jurnal Veteriner; Vol 15 No 1 (2014), 2014)
The aim of this study was to investigate effects of Spirulina phycocyanin on the total  blood cell count,phagocytic activity, and growth of humpback grouper fish, Cromileptes altivelis juvenil.  Fishes were fedwith a diet containing   0, 150, 250, 350 dan 450 mg  phycocyanin per kg diet for four weeks and eachtreatment was triplicates.  Initial body weight  of  grouper was  8.46 ± 0.22 g with a density of 10 fish per56 litre volume. The total count of  erythrocytes and leucocytes increased until the fourth week of rearingperiod. The highest of total erythrocyte and leucocytes were observed in fish treated with 150 mg phycocyaninper kg diet ( 13.17 x  105 cells/mm3 and 8.93 x 105 cells/mm3 respectively) which were not significantlydifferent (P>0.05) to those treated with 250 mg phycocyanin per kg diet. The total leucocytes and phagocyticactivity of fish fed diet containing  250 mg phycocyanin  per kg diet (8.49 x 105 cells/mm3 and 59.67%respectively) were significantly higher  (P <0.05) to those of control group. The highest of final weight(Wt=14.32 g) and weight growth (G=5.89g) and lowest of feed conversion ratio (FCR=1.13) were obtainedin fish treated with  250 mg phycocyanin per kg diet which were  significantly  higher  (P <0.05) than thosefed control diet. The data showed that  the addition of  phycocyanin 250 mg/kg diet enhances the totalleukocyte count, phagocytic activity and the growth of humpback grouper juvenil.
Keywords: Cromileptes altivelis, phycocyanin, leukocytes, phagocytic activity